2022
DOI: 10.3390/ph15091086
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Safety, Off-Target and Bioavailability Profile of the Antiviral Compound Silvestrol

Abstract: We characterized the in vitro safety and bioavailability profile of silvestrol, a compound effective against various viruses, such as corona- and Ebolaviruses, with an EC50 value of about 5 nM. The cytotoxic profile of silvestrol was assessed in various cancer cell lines, as well as the mutagenic and genotoxic potential with Ames and micronuclei tests, respectively. To identify off-target effects, we investigated whether silvestrol modulates G-protein coupled receptor (GPCR) signaling pathways. To predict the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Activation of NF-AT proceeds via IP 3 , calcium release and activation of calcineurin, which dephosphorylates NF-AT at serine residues, initiating its translocation to the nucleus [ 34 ]. Since NF-AT-dependent cytokines were downregulated in T cells, it is possible that the rocaglates investigated here also interfere with the NF-AT signaling pathway, but we could not detect IP 3 or Ca 2+ release in the presence of silvestrol in HEK293T cells [ 35 ]. Proksch et al, also failed to observe Ca 2+ induction in Jurkat T cells with rocaglates [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-AT proceeds via IP 3 , calcium release and activation of calcineurin, which dephosphorylates NF-AT at serine residues, initiating its translocation to the nucleus [ 34 ]. Since NF-AT-dependent cytokines were downregulated in T cells, it is possible that the rocaglates investigated here also interfere with the NF-AT signaling pathway, but we could not detect IP 3 or Ca 2+ release in the presence of silvestrol in HEK293T cells [ 35 ]. Proksch et al, also failed to observe Ca 2+ induction in Jurkat T cells with rocaglates [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, due to its low bioavailability, the oral administration of Silvesterol should be avoided in clinical applications, while topical administration is preferred. 37 Resveratrol can interfere with cell differentiation and inhibit apoptosis by suppressing the activity of STAT3 (Figure 1). Additionally, resveratrol can also inhibit its subsequent pathways by downregulating LMP1.…”
Section: Drugs Targeting Lmp1 Through Affecting the Jak/stat Pathwaymentioning
confidence: 99%
“… 36 It has been suggested that Silvesterol may exhibit mild genotoxicity at higher concentrations, and it is important to further investigate and address these potential side effects. Additionally, due to its low bioavailability, the oral administration of Silvesterol should be avoided in clinical applications, while topical administration is preferred 37 …”
Section: Latent Membrane Proteinsmentioning
confidence: 99%